KAJIAN TERHADAP REVITALISASI KOTA LAMA SEMARANG TAHUN 2020 - Syndu Yoga Pratama; Edi Purwanto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: The revitalization of the old city of Semarang was carried out because of the strong tourism potential when viewed from history and economy, besides that there are regulations regarding conservation that resulted in the Regional Medium-Term Development Plan (RPJMD) in 2016-2021 to respond to the coronation of the old city of Semarang as a tentative list ( 2015) with the aim of the UNESCO World Heritage status. The revitalization with the concept of